EXPLORING DEICTIC EXPRESSIONS IN TROYE SIVAN’S LYRICS - Silitonga, Bahagia Halomoan; Sembiring, Milisi; Sinaga, Pahotan (Prologue: Journal on Language and Literature, 2024)
This research is purposed to find the types and functions of deixis based on Finegan's theory. This study used a descriptive qualitative method approach. The data consisted of some selected songs by Troye Sivan. In collecting the data, the writer searched the song lyrics, downloaded the song lyrics, selected the song lyrics, examined the song lyrics, and classified deixis which is used in the song lyrics based on the types. In analyzing the data, the writer read the data more seriously, tabulated the frequency of each type of deixis, analyzed the data, and drew conclusions. The result of this research indicates there are 2 types and functions of deixis used in Some Selected Song Lyrics by Troye Sivan. There are personal deixis and temporal deixis. There are 373 data found. The first is personal deixis: I (128), me (45), we (28), us (3), our (3), you (106), your (16), yours (12), they (1), him (1), it (17). The second is temporal deixis: this moment forever (1), today (1), now (3), as the days fly by (1), the night before (1), next day (1), someday (1), for the weekend (1). Personal deixis was the most dominant type specifically I (128) data.